Influence of different silica derivatives in the immobilization and stabilization of a Bacillus licheniformis protease (Subtilisin Carlsberg) - Ferreira, L. (2003)
Alcalase 2T, a commercial preparation of Subtilisin Carlsberg, was covalent immobilized onto physiochemically characterized silica supports. The effect of mean pore diameter and surface chemistry on enzyme activity in the hydrolysis of casein has been examined. Two sets of chemically distinct silica supports were used presenting terminal amino (SAPTES) or hydroxyl groups (STESPM-pHEMA). The percentage of immobilized protein was smaller in SAPTES (31-39%) than in STESPM-pHEMA (62-71%), but presented higher total and specific activity. Silicas with large pores (S1000, 130/1200 Å) presented higher specific activities relative to those with smaller pore sizes (S300, 130/550 Å). The influence of glutaraldehyde concentration and the time of enzyme coupling to the S1000SAPTES supports was examined. The apparent Km value for the S1000SAPTES immobilized enzyme is lower than the soluble one which may be explained by the partitioning effects of the substrate. No intraparticle diffusion limitations were observed for the immobilized enzyme and therefore the substrate diffusion does not influence the observable kinetics. Finally, the optimum pH, optimum temperature, thermal stability, operational stability, and storage stability of the immobilized and freely soluble enzymes were compared.